Pigmentary demarcation lines: Three cases encapsulating a benign condition - Natalia Chalupczak; Alexander Woods; Allison Kirchner; Sheryl Hoyer; Roger Haber (Journal of Family Medicine and Primary Care)
Pigmentary demarcation lines (PDL), or Voigt-Futcher lines, are lines marking an abrupt transition between hyperpigmented skin and normal skin. They are usually seen in African, Hispanic, and Japanese populations, but can be rarely observed in Caucasians. The distribution of these markings is postulated to follow “Voigt’s lines,” which mark the underlying peripheral nerves. We report three cases of patients presenting with PDL and review this phenomenon to raise awareness across specialties of this benign condition.